A new species of Deprea Raf. (Solanaceae) from Peru - Cueva, Marco Antonio (2012)
Deprea oxapampensis M. Cueva & I. Treviño (Solanaceae) is described from a specimen collected in Oxapampa (Dpto. Pasco, Peru). The new species is characterized by elliptical leaves 6,5–7,8 × 1,9–2,8 cm, 3–6 axillary flowers, pedicels 11-19 mm long, orange tubular-urceolate corolla with only 5 lobes, calyx 2,7 mm long and elliptical fruit with acrescent calyx adpressed to the berry. We discuss about its relationships with D. ecuatoriana Hunz. & Barboza.